Exosomes derived from Fusobacterium nucleatum-infected colorectal cancer cells facilitate tumour metastasis by selectively carrying miR-1246/92b-3p/27a-3p and CXCL16. Issue 8 (10th November 2020) - Guo, Songhe; Chen, Jun; Chen, Fangfang; Zeng, Qiuyao; Liu, Wan-Li; Zhang, Ge
Abstract : Objective: Exosomes released from tumour cells are packed with unique RNA and protein cargo, and they are emerging as an important mediator in the communication network that promotes tumour progression. The facultative intracellular bacterium Fusobacterium nucleatum (Fn) is an important colorectal cancer (CRC)-associated bacterium. To date, the function of exosomes from Fn-infected CRC cells has not been explored. Design: Exosomes were isolated by sequential differential centrifugation and verified by transmission electron microscopy, NanoSight analysis and Western blotting. Given that exosomes have been shown to transport miRNAs and proteins to alter cellular functions, we performed miRNA sequencing and proteome analysis of exosomes from Fn-infected and non-infected cells. The biological role and mechanism of exosomes from Fn-infected cells in CRC tumour growth and liver metastasis were determined in vitro and in vivo. Results: We demonstrated that exosomes delivered miR-1246/92b-3p/27a-3p and CXCL16/RhoA/IL-8 from Fn-infected cells into non-infected cells to increase cell migration ability in vitro and promote tumour metastasis in vivo. Finally, both circulating exosomal miR-1246/92b-3p/27a-3p and CXCL16 levels were closely associated with Fn abundance and tumour stage in patients with CRC. Conclusion: This study suggests that Fn infection may stimulate tumour cells to generate miR-1246/92b-3p/27a-3p-rich and CXCL16/RhoA/IL-8 exosomes that are delivered to uninfected cells to promote prometastatic behaviours.